RANK DETERMINATION APPLICATION IN INDONESIA TWO WHEEL RACER WITH MICROSOFTACCESS - Eni Setiawati; Susi Wagiyati P, SKom, MMSI (Jurnal Sistem Informasi, 2002)
Microsoft Access is an object-oriented programming. Therefore, its use in a programmer to create application programs. Microsoft Access is designed with a certain arrangement so that when activated, does not open all its facilities. With Microsoft Access applications for two-wheel racer ranking in Indonesia, the data processing activities can be carried out smoothly and more efficiently.